Phosphorylation of guanosine monophosphate reductase triggers a GTP-dependent switch from pro- to anti-oncogenic function of EPHA4. Issue 6 (16th June 2022) - Wolff, David W.; Deng, Zhiyong; Bianchi-Smiraglia, Anna; Foley, Colleen E.; Han, Zhannan; Wang, Xingyou; Shen, Shichen; Rosenberg, Masha M.; Moparthy, Sudha; Yun, Dong Hyun; Chen, Jialin; Baker, Brian K.; et al.
Summary: Signal transduction pathways post-translationally regulating nucleotide metabolism remain largely unknown. Guanosine monophosphate reductase (GMPR) is a nucleotide metabolism enzyme that decreases GTP pools by converting GMP to IMP. We observed that phosphorylation of GMPR at Tyr267 is critical for its activity and found that this phosphorylation by ephrin receptor tyrosine kinase EPHA4 decreases GTP pools in cell protrusions and levels of GTP-bound RAC1. EPHs possess oncogenic and tumor-suppressor activities, although the mechanisms underlying switches between these two modes are poorly understood. We demonstrated that GMPR plays a key role in EPHA4-mediated RAC1 suppression. This supersedes GMPR-independent activation of RAC1 by EPHA4, resulting in a negative overall effect on melanoma cell invasion and tumorigenicity. Accordingly, EPHA4 levels increase during melanoma progression and inversely correlate with GMPR levels in individual melanoma tumors. Therefore, phosphorylation of GMPR at Tyr267 is a metabolic signal transduction switch controlling GTP biosynthesis and transformed phenotypes. Graphical abstract: Highlights: GMPR is activated by phosphorylation at Tyr267, causing depletion of GTP pools EPHA4, GMPR, and RAC1 colocalize in the cell EPHA4 phosphorylates GMPR, leading to decreased RAC1 activity and cell invasion EPHA4 pro- versus anti-oncogenic function depends on GMPR phosphorylation status Abstract : Wolff et al. demonstrate that phosphorylation of guanosine monophosphate reductase (GMPR) by Ephrin receptor A4 (EPHA4) regulates GMPR enzymatic activity, intracellular GTP levels, RAC1 activation, and melanoma cell invasion. The phosphorylation status of GMPR acts as a switch influencing the net pro- versus anti-oncogenic effects of EPHA4.